2022
DOI: 10.7759/cureus.28162
|View full text |Cite
|
Sign up to set email alerts
|

Cardiotoxicity Associated With Chimeric Antigen Receptor (CAR)-T Cell Therapy for Hematologic Malignancies: A Systematic Review

Abstract: Chimeric Antigen Receptor (CAR)-T cell therapy has been one of the most important breakthroughs for treating hematologic malignancies. On the other hand, the therapy had many toxicities. One of the toxicities of the CAR-T therapy is cardiotoxicity. The goal of the systematic review is to elaborate on the cardiotoxicities related to CAR-T therapy for hematologic malignancies. The systematic review is following the Preferred Reporting Items for Systematic Review and Meta-Analyses (PRISMA) 2020 guidelines. The sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Additionally, CAR-T therapy has been associated with cardiotoxic adverse effects, especially in populations with preexisting risk factors, like prior cardiac history and dyslipidemia, among others [27]. The most common adverse effects are mediated by cytokine release syndrome and are arrhythmias, heart failure, and sudden cardiac arrest [28]. Understanding that Hispanic patients have relatively poorer access to various treatment options for NHL is critical in explaining the lower odds ratio of various MACCEs, including AMI and AF.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, CAR-T therapy has been associated with cardiotoxic adverse effects, especially in populations with preexisting risk factors, like prior cardiac history and dyslipidemia, among others [27]. The most common adverse effects are mediated by cytokine release syndrome and are arrhythmias, heart failure, and sudden cardiac arrest [28]. Understanding that Hispanic patients have relatively poorer access to various treatment options for NHL is critical in explaining the lower odds ratio of various MACCEs, including AMI and AF.…”
Section: Discussionmentioning
confidence: 99%
“…Cardiovascular toxicity is not uncommon in patients receiving CAR-T cells therapy (52). Adam Goldman et al (47) found that the occurrence of tachyarrhythmia was a major adverse effect of the heart.…”
Section: Cardiovascular Toxicitiesmentioning
confidence: 99%
“…Cardiovascular toxicity is not uncommon in patients receiving CAR-T cells therapy ( 52 ). Adam Goldman et al.…”
Section: Clinical Presentation Of Saes Associated With Car-t Cells Th...mentioning
confidence: 99%